Pectoralis Minor Index: Does Ethnicity Hold Relevance? Estimation of Pectoralis Minor Length in the Indian Population and Its Correlation with Hand Length - Sharma, Amit (Indian J Orthop, 2020)
OBJECTIVE: Pectoralis Minor Index (PMI) is a proposed parameter to evaluate the pectoralis minor length (PML), eliminating the effect of subject’s variability of height. Neither a PMI standard value nor any cutoff value to label a shortened pectoralis minor (PM) has been accepted yet, which can be applied to every individual. Moreover, the length of the PM has never been correlated to any fixed reference in the body. Hence, we estimated the PML in the Indian population and investigated its correlation to the individual’s hand length. METHODOLOGY: A cross-sectional study was conducted including 100 adult subjects without any shoulder pathology. Subjects with history of fracture/treatment involving upper limb/spine were excluded. Two assessors evaluated the height, PM length and hand length of subjects. PMI and hand correlation was evaluated using their mean values. RESULTS: Mean PML and PMI for dominant and non-dominant shoulder were calculated to be 18.11/18.21 cm and 10.53/10.59, respectively. Mean hand length of dominant and non-dominant hand was found to be 18.27 cm and 18.31 cm, respectively. Pearson correlation coefficient between right/left PML with right/left hand length was 0.67 and 0.63, respectively, suggesting a good correlation (p < 0.01). CONCLUSIONS: PMI varies in different ethnic groups, which makes PMI a less reliable indicator for managing shoulder pain in ethnic groups where reference values are yet not available. Contralateral PMI can be used as a reference value in unilateral shoulder pathologies with short PML. Hand length can become an important parameter in evaluating painful shoulders even in bilateral pathologies. Hand length can be used as an easy and quick technique to compare the PML and effect of physiotherapy in patients with diagnosis of short PML, attending follow-up OPD. Though, a study comparing PML of normal subjects and patients with shoulder pain will be further required in different ethnic groups for further validation of this study.